Intense laser field effect on impurity states in a semiconductor quantum well: transition from the single to double quantum well potential (2011)
ABSTRACT: In this work are studied the intense laser effects on the impurity states in GaAs-Ga1−xAlxAs quantum wells under applied electric and magnetic fields. The electric field is taken oriented along the growth direction of the quantum well whereas the magnetic field is considered to be in-plane. The calculations are made within the effective mass and parabolic band approximations. The intense laser effects have been included through the Floquet method by modifying the confinement potential associated to the heterostructure. The results are presented for several configurations of the dimensions of the quantum well, the position of the impurity atom, the applied electric and magnetic fields, and the incident intense laser radiation. The results suggest that for fixed geometry setups in the system, the binding energy is a decreasing function of the electric field intensity while a dual monotonic behavior is detected when it varies with the magnitude of an applied magnetic field, according to the intensity of the laser field radiation.